ISOLASI KITIN, KARAKTERISASI, DAN SINTESIS KITOSAN DARI KULIT UDANG - Agustina, Sry; Swantara, I Made Dira; Suartha, I Nyoman (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015, 2015)
Chitosan is the modification of chitin which found on the outer skin of Crustacea species such as shrimps and crabs. This study aims to isolate chitin, syntesize and charactetize chitosan from shrimp shells. Chitin isolation stage included demineralization using HCL 1.5M and deproteination step with NaOH 3.5%. Transformation of chitin into chitosan was done through the deacetylation reaction by using NaOH 60%. The result showed that characteristic of the chitosan obtained in this research was as follows: the yield of transformation chitin into chitosan was 67.08%; it had a white color powder texture with had no smell; water content 1.55%; It solubled in 2 % acetic acid with 84.85 % deacetylation.
Keywords: Chitin, Chitosan, Shrimp shell